PENGEMBANGAN PERANGKAT LUNAK SIMULASI KOMPUTER SEBAGAI ALAT BANTU DALAM ANALISIS FARMAKOKINETIK - Handari, Bevina D; Djajadisastra, Joshita; Silaban, Denny Riama (UI Scholars Hub, 2006)
The Development of a Computer Simulation Software as a Tool in Pharmacokinetics Analisys. This research uses mammilary model (one compartment and two compartments) as compartment model in which a single drug administration is given via oral and intravenous. Mathematical modeling in differential equations can be derived from a pharmacokinetics model. The solutions are pharmacokinetics variables and parameters that can be solved using some mathematical and numerical methods such as Laplace transformation, residual method, superposition principle, trapezoidal rule and some solving methods in differential equations.To overcome manual calculation and to visualize a drug’s dynamics in the graph form, a computer simulation software based on Visual Basic has been built. The simulation results show that any particular sample data plasma can be checked whether it is given orally or injection and has a tendency to be compatible with an assumption of one compartment or two compartments. For urin data, the software capability is still limited only for one compartment. However, it can checked if the corresponding data is given via oral or injection. So the simulations show that pharmacokinetics variables and parameters will have individual effects